2014
DOI: 10.2340/00015555-1753
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Skin Cancer in Psoriasis Patients Treated with UVB Therapy

Abstract: Phototherapy is an effective and widely used treatment for generalised plaque psoriasis. Despite the mutagenic effects of UVB this type of therapy is still assumed to be a safe treatment option. We have performed a cross sectional study to assess the risk of skin cancer in the cohort of psoriasis patients treated with UVB. A total of 162 white patients (116 men and 46 women, mean ± standard deviation age 56.0 ± 13.5 years) were included in the study. All patients have previously been treated with UVB at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…Another publication suggested a lower risk for metastasis in a human melanoma cell line in mice treated with MTX . In a previous study from our group, we found that the risk of skin cancer, including melanoma, in patients with psoriasis treated with UVB therapy correlated with the number of treatments (controlling for age), but the overall risk of malignancy was not higher than in the general population …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Another publication suggested a lower risk for metastasis in a human melanoma cell line in mice treated with MTX . In a previous study from our group, we found that the risk of skin cancer, including melanoma, in patients with psoriasis treated with UVB therapy correlated with the number of treatments (controlling for age), but the overall risk of malignancy was not higher than in the general population …”
Section: Discussionmentioning
confidence: 52%
“…23 In a previous study from our group, we found that the risk of skin cancer, including melanoma, in patients with psoriasis treated with UVB therapy correlated with the number of treatments (controlling for age), but the overall risk of malignancy was not higher than in the general population. 24 It is important to mention that no patient with MTX as antineoplastic treatment could have been included in the study, because these treatments are given in an inpatient setting and therefore are not included in the present study. Analysing the results in the study, it is instrumental to mention the risk for surveillance bias, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that UVBirradiation without UVA is less efficient in inducing skin carcinogenesis. As a matter of fact, UVB phototherapy is not associated with a significant cancer risk (26,27). The increased evidence that UVA could be involved in carcinogenesis is worrisome because of the high percentage of UVA emitted by modern tanning devices (16).…”
Section: Discussionmentioning
confidence: 99%
“…Latest data suggests patients with more severe psoriasis have an increased risk of cancer-related mortality, this association being the strongest for lymphoproliferative malignancies and cutaneous malignancies [50,51]. The increased risk is likely linked to male gender, advancing age or COPD in patients with psoriasis arthritis [53].…”
Section: Screening For Cancersmentioning
confidence: 99%